(3edA GdYjHI ajeG LeY HWhd GdZjHI aj GdQMdI Edi ecI hWjHIs - (3eMeO Hf YeQ Hf eMeO, CHh YHO Gddg, eMH GdOjf GHf QTjO GdagQj GdSHJj,J (B721 (3g` s
(3ChdgG (B:s
(3haef dbjfGg CjVkG HKZQ GdCScfOQjI LeGd GdOjf CHh YHO Gddg eMeO GdHhfi GdTQGHi GdeJWHH ai CNdGbI TcGSI hcHQ hYOe age s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg bjd dg CNHQce CHh GdMSf YHO GdQMef Hf eMeO Hf GdeXaQ Hf eYGP GdOGhOi bQGAI Ydjg hCfJ JSeY s
(3HChdgG Jedc dCMO CUaGO CMeO Hf jMji Hf eMeO GdhfTQHSi GdeJhai (B914 (3g`s
(3hUdJg SfI (B683 (3hai cX (B2/ 1813 : (3PcQ ajg ef CNP Yfg hSeY efg hdbjg aLGA eTJedkG Ydi afhf ai SJ eLdOGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B93s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B317 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B344 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B189 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B836s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs